(untitled) (Research, Society and Development, 2024)
This study aimed to develop and evaluate gelatin membranes enriched with barbatimão (Stryphnodendron adstringens) plant extract as a biomaterial for surgical wound healing. The hydroethanolic extract of barbatimão was obtained through dynamic maceration. The concentration of total phenols was quantified, and its antimicrobial activity was evaluated in vitro against Staphylococcus aureus and Streptococcus pyogenes. The membranes were prepared based on gelatin in acetic acid solution, glycerol, and barbatimão extract. Membranes were made without extract and with extract at different concentrations (200 mg and 800 mg), cut into 12 mm diameter discs, and stained with fluorescein. Wistar rats were used for experimentation, divided into four groups: I (control), II (membrane without extract), III (200 mg), and IV (800 mg). A 10mm diameter surgical wound was made on the animals’ backs until reaching the muscular layer. The wounds were treated according to the experimental design. The membrane over the wound was monitored by fluorescein marking. The wound diameter reduction was measured after 7, 14, and 21 days of experimentation. Barbatimão extract showed a rich concentration of phenolic compounds and activity against S. aureus. The membrane exhibited adaptability to the surface of cutaneous lesions, with adhesion exceeding 7 days and less than 14 days. The results indicate that the developed membrane possesses properties that promote the healing of surgical cutaneous lesions through the retraction index.